The Reliability of the Thai version of Health-Related Quality of Life Questionnaire: PedsQL 3.0 Cancer Module - Khemika Khemakanok Sudnawa MD; Jitthip Yeepae MD; Apichat Photia MD; Piya Rujkijyanont MD; Chanchai Traivaree MD, MSc; Chalinee Monsereenusorn MD (SAGE Publishing, 2022)
Assessing the health-related quality of life (HRQOL) is highly recommended as a standard of care for children with cancer in conjunction with medical treatment. The Pediatric Quality of Life Inventory (PedsQL) Cancer Module is a standard tool designed to assess the HRQOL among pediatric oncology patients. This study aimed to evaluate the reliability and correlation of the PedsQL 3.0 Cancer Module in Thai version between child and parent reports. A cross-sectional study was conducted on 85 Thai children with cancer and their families. Excellent internal consistency of the PedsQL 3.0 Cancer Module of the Thai version was addressed among child and parent reports (0.92 and 0.94, respectively). Overall positive correlations were also found between child and parent reports ( r = 0.61, P < .001). However, the statistically significant differences of HRQOL scores between child and parent reports were determined on procedural anxiety (70.05 ± 26.67 vs 60.03 ± 25.6, P = .003), treatment anxiety (88.15 ± 17.37 vs 76.82 ± 26.7, P = .001), worry (66.67 ± 25.59 vs 55.34 ± 30.37, P = .003) and the total score (74.37 ± 15.7 vs 70.42 ± 17.15, P = .034). This study demonstrated desirable internal reliability with positive correlations between child and parent reports of the PedsQL 3.0 Cancer Module in Thai version, although possible differences between child and parent HRQOL scores should be considered.